Incidence of Elbow Injury Patterns in Japanese Adolescent Judo Players: Analysis from a Nationwide Insurance Database - Akira Ikumi; Eiji Sasaki; Naoki Sakuyama; Yasuo Mikami (MDPI AG, 2024)
Elbow injuries are common in judo, particularly among adolescents. This study investigated the incidence and patterns of three types of elbow injuries (sprain, dislocation, and fracture-dislocation) among Japanese adolescent judo players (12 to 18 years old) using data from a nationwide insurance database, covering the period from 2010 to 2019. A total of 4614 elbow injuries were recorded, with sprains being the most frequent (67.6% of cases). Female players had a 20% higher incidence of sprains than male players (6.8 vs. 5.4 per 1000 athlete-years). Severe injuries, such as dislocations and fracture-dislocations, were more common in high school players, with male middle school students exhibiting a higher rate of elbow fracture-dislocations (+15%) compared with female students. Elbow injuries frequently occurred during te-waza techniques, particularly seoi-nage, when players extended their arms to prevent being thrown. Peripheral nerve injuries, predominantly ulnar nerve injuries, accompanied elbow dislocations in 74% of the cases. This study highlights the importance of proper instruction in defensive and ukemi techniques, particularly those that discourage the use of hands to prevent falls during throws, to reduce the risk of elbow injuries.